An 11-Year-Old Male with Refractory Osteomyelitis - Clifford T. Mauriello; Ole A. Raustol; Maria A. Aguiar; Kenji M. Cunnion (Hindawi Limited, 2012)
We present a case of empirical treatment failure for chronic osteomyelitis in a previously healthy 11-year-old male involving the distal phalanx of the right first digit. After initial debridement, empiric antibiotics were started for presumed Staphylococcus aureus infection. Operative bacterial cultures yielded no growth. Despite three weeks of antistaphylococcal antibiotics the patient's symptoms worsened and the destruction of bone progressed. A repeat plain X-ray revealed a new lesion in the proximal phalanx of the right second digit. The recognition of multifocal osteomyelitis led to reexamination of bone tissue specimens using special stains which demonstrated rare broad-based budding yeast. Fungal cultures eventually grew Blastomyces dermatitidis. Treatment with amphotericin B led to rapid clinical improvement. This case illustrates that clinicians must remain vigilant for warning signs that empiric treatment may be failing for presumptive Staphylococcus aureus, provoking reconsideration of the differential diagnosis and an intensification of efforts to evaluate for alternative etiologies.